Pemasaran Jasa Pendidikan sebagai Strategi Dayah Bulisc dalam Meningkatkan Daya Saing Madrasah - Ade Kurniawan (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
Dayah BULISC is a new educational institution in the West Aceh region, but in a short time, the Dayah has been able to establish itself as one of the institutions that are in demand by the community. This fact is then interested to be investigated. This research is a qualitative research with a case study approach. Data was collected using observation, interviews, and document searches. The results of the study show that Dayah BULISC has been able to apply the marketing mix (product, people, price, promotion, place, physical evidence, process) well in building the quality of institutions while increasing inter-institutional competitiveness. This can be seen. The product chosen by Dayah BULISC with the flagship program is the Tahfizul Quran. Dayah BULISC  has good resources and is supported by cheap and affordable tuition fees for the community. The location of Dayah is also very strategic with the condition of the building being quite good and complete in supporting the learning carried out. Dayah BULISC also conducts promotions using several media including social media so that messages about the conditions and programs that are carried out by Dayah can be conveyed in full to the community